Analysis of Factors Related to the Role of Nurses as Care Givers in the Implementation of Patient Safety: Analisis - Dewi Wulandari; Ixora Ixora (Poltekkes Kemenkes Malang, 2025)
Nurses in carrying out their role as care givers have the task of caring for patients, making decisions, communicating and collaborating with other health teams. The Emergency Room is part of the hospital that provides initial treatment for patients. The implementation of patient safety carried out by nurses is a form of compliance in every action or interaction with patients in accordance with a compliance theory or known as the